Impact of community-level socioeconomic disparities on quality of life after burn injury: A Burn Model Systems Database study. Issue 4 (June 2023) - Mason, Stephanie; Gause, Emma; McMullen, Kara; Murphy, Sha'Chia; Sibbett, Stephen; Holavanahalli, Radha; Schneider, Jeffrey; Gibran, Nicole; Kazis, Lewis E.; Stewart, Barclay T.
Abstract: Introduction: Individual-level socioeconomic disparities impact burn-related incidence, severity and outcomes. However, the impact of community-level socioeconomic disparities on recovery after burn injury is poorly understood. As a result, we are not yet able to develop individual- and community-specific strategies to optimize recovery. Therefore, we aimed to characterize the association between community-level socioeconomic disparities and long-term, health-related quality of life after burn injury. Methods: We queried the Burn Model System National Longitudinal Database for participants who were> 14 years with a zip code and who had completed a health-related quality of life (HRQOL) questionnaire (VR-12) 6 months after injury. BMS data were deterministically linked by zip code to the Distressed Communities Index (DCI), which combines seven census-derived metrics into a single indicator of economic well-being, education, housing and opportunity at the zip code level. Hierarchical linear models were used to estimate the association between community deprivation and HRQOL 6 months after burn injury, as measured by mental (MCS) and physical (PCS) component summary scores of the SF12/VR12. Results: 342 participants met inclusion criteria. Participants were mostly male (n = 239, 69 %) and had a median age of 48 years (IQR 33–57 years). Median %TBSA was 10 (IQR 3–28). More than one-third of participants (n = 117, 34 %) lived in a community within the highest two distress quintiles. After adjusting for age, race/ethnicity, number of trips to the operating room (OR) and pre-injury PCS, neighbourhood distress was negatively associated with 6-month PCS (ß-0.05, 95 % CI [−0.09, −0.01]). Increasing age and lower pre-injury PCS were also negatively associated with 6-month PCS. There was no observed association between neighbourhood distress and 6-month MCS after adjustment for age, participant race/ethnicity, number of trips to the OR and pre-injury MCS. Higher pre-injury MCS was associated with 6-month MCS (ß0.54, 95 % CI [−0.41, 0.67]). Conclusions: Community distress is associated with lower PCS at 6 months after burn injury but no association with MCS was identified. Pre-injury HRQOL is associated with both PCS and MCS after injury. Further study of the factors underlying the relationship between community distress and physical functional recovery (e.g., access to rehabilitation services, availability of adaptations) is required to identify potential interventions. Highlights: Community-level exposures impact individuals' risk of complicated recovery. Individuals from distressed communities have worse outcomes after burn injury. Understanding community disadvantage can facilitate allocation of resources.